Hospital discharge data for assessing myocardial infarction events and trends, and effects of diagnosis validation according to MONICA and AHA criteria. Issue 5 (19th October 2010) - Barchielli, Alessandro; Balzi, Daniela; Naldoni, Paola; Roberts, Anna Teresa; Profili, Francesco; Dima, Francesco; Palmieri, Luigi
Abstract : Background: Acute myocardial infarction (AMI; ICD9-CM 410*) is a leading cause of morbidity and mortality all over the world, and its community surveillance is essential to monitor variation in the occurrence of the disease. Between the late 1990s and the early 2000s more sensitive and specific biomarkers of myocardial necrosis (ie, troponins) were introduced and new diagnostic criteria, emphasising the role of biomarkers, have been developed for clinical and epidemiological purposes. Methods: Tosc-AMI is a population-based registry based on the record linkage between hospital and mortality databases; it provides trends of coronary events in Tuscany, Italy. Two random samples of patients admitted to hospital in 2003 were validated according to the American Heart Association (AHA; 2003) and the Multinational MONItoring of trends and determinants in CArdiovascular disease (MONICA) (1983) criteria. Sample 1 (380 cases) was represented by patients admitted to hospital for AMI and sample 2 (380 cases) for other coronary diagnosis. Results: Tosc-AMI attack rates increased from the period 1997 to 2005 (men: +17%; women: +30%) and then they decreased in the following 2 years (men: −8%; women: −13%). The rise of AMI hospital admissions was due to cases with ICD9-CM code 410.7 (largely representing non-ST elevation MI). According to the AHA criteria, 94.6% events of sample 1 and 29.8% events of sample 2 fulfilled the most extensive criteria for definite, probable or possible AMI. As expected, the more updated AHA definition identified as definite AMI an additional 33.3% when compared to the MONICA criteria (86.0% vs 52.7%). Conclusions: The study suggests an influence of the new diagnostic criteria on the rising AMI trend observed in the early 2000s, an increase of less severe cases and a decreasing trend of forms with a more extended myocardial damage.